Improvements in logistics could increase survival after out‐of‐hospital cardiac arrest in Sweden. (14th March 2013) - Strömsöe, A.; Afzelius, S.; Axelsson, C.; Södersved Källestedt, M. L.; Enlund, M.; Svensson, L.; Herlitz, J.
Abstract Objectives In a review based on estimations and assumptions, to report the estimated number of survivors after out‐of‐hospital cardiac arrest (OHCA) in whom cardiopulmonary resuscitation (CPR) was started and to speculate about possible future improvements in Sweden. Design An observational study. Setting All ambulance organisations in Sweden. Subjects Patients included in the Swedish Cardiac Arrest Registry who suffered an OHCA between January 1, 2008 and December 31, 2010. Approximately 80% of OHCA cases in Sweden in which CPR was started are included. Interventions None Results In 11 005 patients, the 1‐month survival rate was 9.4%. There are approximately 5000 OHCA cases annually in which CPR is started and 30‐day survival is achieved in up to 500 patients yearly (6 per 100 000 inhabitants). Based on findings on survival in relation to the time to calling for the Emergency Medical Service (EMS) and the start of CPR and defibrillation, it was estimated that, if the delay from collapse to (i) calling EMS, (ii) the start of CPR, and (iii) the time to defibrillation were reduced to <2 min, <2 min, and <8 min, respectively, 300–400 additional lives could be saved. Conclusion Based on findings relating to the delay to calling for the EMS and the start of CPR and defibrillation, we speculate that 300–400 additional OHCA patients yearly (4 per 100 000 inhabitants) could be saved in Sweden.